Legal Study Of Worker Protection Against Unilateral Termination Of Employment : Case Study Of Decision Number 21/PDT.SUS-PHI/2025/PN.SRG - Fatih Arif Mutaqin; M. Nassir Agustiawan; Mohammad Hifni (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
Unilateral termination of employment (PHK) carried out by employers without proper legal procedures constitutes a violation against workers and can lead to labor disputes. This study aims to analyze the legal basis for worker protection resulting from unilateral layoffs and to understand the legal considerations of the panel of judges in deciding the case based on Serang District Court Decision Number 21/Pdt.Sus-PHI/2025/PN SRG. This study uses a normative legal method with a case study approach, supplemented by qualitative analysis of primary and secondary data. Primary data were obtained from court ruling documents, while secondary data included laws and regulations, books, legal journals, and teaching materials. The analysis was conducted descriptively and prescriptively to evaluate the conformity between the judge's application of the law and applicable positive legal norms. The research results indicate that the judge, in deciding this case, applied legal aspects, referring to the provisions of Articles 151, 153, and 158 of Law No. 13 of 2003 as the primary consideration. The panel of judges declared the unilateral layoffs by the employer invalid because they failed to meet formal and material requirements, thus granting the workers their full rights, including wages, during the industrial relations dispute. However, the judge failed to fully consider sociological and philosophical aspects, such as the workers' economic conditions and the principle of "greater protection" for workers as the more vulnerable party